The Chronicles of Narnia the silver chair - Lewis, C. S. (Harper Collins London, 2009)
When old King Caspian's only son and heir Prince Rilian disappears, Aslan calls on Eustace and Jill to search for the lost Prince. On their quest the children meet up with Puddleglum, a marshwiggle, and their search leads them underground, where they must face the Green Witch - the Queen of the Deep Realm